Does Foreign Aid Have an Expected Role in the Economic Growth of Bangladesh? An Analysis in ARDL Approach - Hossain, Md Ismail; Hossain , Md Istiak; Islam , Mollah Aminul; Sultanuzzaman, Md Reza (International Journal of Economics and Financial Issues, 2022)
Bangladesh, a lower-middle-income country in South Asia and expected to be a developing country by 2024, is one of the most densely populated countries in the world, with 166.30 million (WDI, 2021) people. Foreign Aid (FA) plays a vital role in the economic development of Bangladesh. Foreign Aid, loans, and grants generally, which we call Official Development Assistance (ODA) (in this study, we have used the term ’Foreign aid’) have increased gradually over the years after the liberation of Bangladesh with the increase of per capita GDP. In our study, we have conducted a single country investigation on Bangladesh and examined the impact of Foreign Aid on the Economic growth of Bangladesh from 1971 to 2019. The ARDL bounds test methodology was applied in the study, followed by the unit root test and the bound test for cointegration. Several diagnostic tests were conducted to check the stability and reliability of the model. The obtained results revealed that Foreign Aid has a significant and positive impact on the Economic growth of Bangladesh in the long- and short-run. The coefficients of the variables of our study refer that a 1(one) unit increase in foreign Aid would intensify 0.24 units of Economic growth in Bangladesh. In line with Foreign Aid, Gross capital formation also has a significant positive impact on the country’s economic development. On the contrary, trade openness has a negative but insignificant impact both in the short and long run. Besides, population growth negatively and significantly impacts economic growth in the long run. In this study, finally, we have recommended some policy implications for the Government of Bangladesh.